Anaplastic Large Cell Lymphoma of the Breast With Simultaneous Peripheral Blood and Marrow Involvement. Issue 1 (January 2022) - Dhanasekaran, Venkatesh; Srinivas, Bheemanathi Hanuman; Basu, Debdatta; Dubashi, Biswajit; Gochhait, Debasis
Abstract: Anaplastic large cell lymphoma (ALCL) of the breast is an extremely rare hematolymphoid malignancy and is characteristically associated with breast implants. Among the primary hematolymphoid malignancies arising from the breast, T-cell lymphomas are extremely rare, and among T-cell lymphomas, ALCL has a better prognosis. We present the case of a 30-year-old woman with a diagnosis of ALCL without any breast implants and with simultaneous involvement of bone marrow and peripheral blood. Pathologists should be aware of this entity and should include it in the differential diagnoses when evaluating a breast biopsy that shows a high-grade anaplastic morphology.